2022
DOI: 10.3389/fmed.2022.915399
|View full text |Cite
|
Sign up to set email alerts
|

Time to healthcare seeking following the onset of symptoms among men and women attending a sexual health clinic in Melbourne, Australia

Abstract: BackgroundTimely diagnosis and treatment of sexually transmitted infections (STIs) underpin their control by reducing the duration of infectiousness. There are currently limited data exploring healthcare seeking among individuals with STI symptoms.MethodsWe analyzed data on individuals reporting STI symptoms at the Melbourne Sexual Health Centre (MSHC) between August 2017 and December 2020. We calculated the time between symptom onset and clinic attendance by risk group for 13 STI diagnoses. We performed univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This result is not surprising, as past studies have shown that MSW are less likely to seek health care compared with women. The reasons, however, are complex and may include a culture that promotes a unrealistic view of masculinity and self-reliance, [14][15][16][17][18][19] but also women may be more likely to take care of their sexual health because of other reasons such as pregnancies, regular cervical screening, and contraception 20 which they may more proactively attempt to gain a better understanding of sexual health issues. As such, this may result in women being more likely to consent to SHAVE to have a record documenting their sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not surprising, as past studies have shown that MSW are less likely to seek health care compared with women. The reasons, however, are complex and may include a culture that promotes a unrealistic view of masculinity and self-reliance, [14][15][16][17][18][19] but also women may be more likely to take care of their sexual health because of other reasons such as pregnancies, regular cervical screening, and contraception 20 which they may more proactively attempt to gain a better understanding of sexual health issues. As such, this may result in women being more likely to consent to SHAVE to have a record documenting their sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that delayed health care-seeking behavior, defined as symptom duration greater than seven days following the onset of STI-associated symptoms, is common (28-82% of cases). 28 Such a delay can be due to multiple factors, like the asymptomatic nature of some STIs, lack of knowledge, stigma, easy accessibility to pharmacies, self-medication, and superstition beliefs in our part of the world.…”
Section: Discussionmentioning
confidence: 99%